Universal Chlamydia Screening for Women With Threatened Preterm Labor: A Cost-Effectiveness Analysis [14M]. (May 2017) - Gimovsky, Alexis; Berghella, Vincenzo; Werner, Erika
Abstract : INTRODUCTION: To estimate the cost and effect of universal chlamydia (CT) screening compared to no CT screening for women presenting with threatened preterm labor in the United States. METHODS: We created a decision model comparing universal screening for CT versus no CT screening for women presenting with threatened preterm labor. Assumed probabilities included incidence of CT in women with preterm labor of 12% and a conditional probability of congenital CT of 60%. Primary outcome was the cost to prevent one case of neonatal chlamydia. A strategy was considered cost-effective if cost was < $100, 000 to prevent one case of congenital chlamydia. One way sensitivity analyses and Monte-Carlo simulations assessed the robustness of the model. RESULTS: Screening for CT at the time of threatened preterm labor was cost saving, saving $17, 202, 570 and preventing 6, 624 cases of neonatal chlamydia and 1, 268 cases of preterm birth/100, 000 women screened. One way sensitivity analysis revealed that the model was sensitive to incidence of maternal CT and cost of CT screening and treatment. CT screening remained cost saving when the incidence of maternal CT was >1%. Monte Carlo analyses revealed that screening was cost-saving in 87.3% of simulations, cost effective, but not cost-saving in an additional 3.5% of simulations, and not cost-effective 9.1% of the time. CONCLUSION: Screening for CT at time of presentation for threatened preterm labor in the United States is cost saving in the majority of conditions. Only in populations at extremely low risk for Chlamydia does it decrease health care costs to defer CT testing.